2021
DOI: 10.3390/su132212833
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkalis on Natural Carbonation of Limestone Calcined Clay Cement Pastes

Abstract: Vulnerability to atmospheric carbonation is one of the major durability concerns for limestone calcined clay cement (LC3) concrete due to its relatively low overall alkalinity. In this study, the natural carbonation behaviors of ternary ordinary Portland cement-metakaolin-limestone (OPC-MK-LS) blends containing various sulfate salts (i.e., anhydrous CaSO4, Na2SO4, and K2SO4) are studied, with the aim of revealing the influence of alkali cations (Na+, K+). Detailed analyses on the hydrated phase assemblage, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…This results in a nonuniform distribution of mechanical properties, leading to a certain variability in compressive strength measurements. Moreover, the slightly larger error bars in the compressive strength of the bare cement cube suggest inherent material and procedural variabilities, as also reported in the literature. This emphasizes the importance of precise sample preparation and consistent testing protocols.…”
Section: Resultssupporting
confidence: 57%
“…This results in a nonuniform distribution of mechanical properties, leading to a certain variability in compressive strength measurements. Moreover, the slightly larger error bars in the compressive strength of the bare cement cube suggest inherent material and procedural variabilities, as also reported in the literature. This emphasizes the importance of precise sample preparation and consistent testing protocols.…”
Section: Resultssupporting
confidence: 57%
“…As a result, this case also applies to LC 3 -50 cement-based concrete, which has a higher carbonation rate than OPC [11]. A Chinese study suggested that a low amount of calcium in LC 3 -50 cement comparatively OPC can be the reason for the lower binding capacity of carbon dioxide and having more carbonation depth in the LC 3 -50 system [32]. Figure 8(a) shows the LC 3 -50 and OPC samples kept in the carbonation chamber for exposure to 5% carbon dioxide up to 24 weeks.…”
Section: Carbonationmentioning
confidence: 85%
“…As shown in Table 1, the reference LC 3 paste (as control) was formulated by blending OPC, calcined kaolinite (metakaolin, MK), limestone (LS), and anhydrite calcium sulfate (Cs) powders at a mass ratio of 52.5:30:15:2.5 (following the work of reference [17]). To study the influence of MgO addition on the properties of LC 3 pastes, three incorporation dosages, including 2.5%, 5%, and 7.5% by powder mass (powder means the summation of anhydrous OPC+MK+LS+Cs) were considered, and the corresponding mixes were denoted as LC 3 _2.5M, LC 3 _5M, and LC 3 _7.5M, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although LC 3 has been shown to possess excellent long-term mechanical and, on some occasions, superior durability performance (particularly the chloride and sulfate resistance) than conventional OPC [12][13][14], it tends to have relatively poor carbonation resistance [9,[15][16][17], thus increasing the corrosion risk of reinforcing steel embedded in carbonated concrete. The comparatively poor carbonation resistance of LC 3 primarily originates from a low amount of portlandite, which serves as a pH buffer in carbonating concrete.…”
Section: Introductionmentioning
confidence: 99%